Internal Quality Assurance System in Indonesia Higher Education: Literature Review - Sampe, Novihta; Arifin, Zainal (Universitas Pendidikan Ganesha, 2024)
The importance of Quality Assurance (QA) is increasing worldwide, particularly in developed countries where products and services are prominent. The aims of this study analyze a comprehensive and essential comprehension of Internal Quality Assurance in Indonesian Higher Education Institutions (HEIs). The main approach utilised in this study involved doing a literature review, wherein relevant literature from many reliable sources was identified and subsequently filtered based on its relevance. This study emphasises four research topics that warrant thorough investigation. The implementation of the SPMI (System of Internal Quality Assurance) in multiple Higher Education Institutions (HEIs) has been effectively executed, with the involvement of quality assurance bodies at the university, faculty, and study programme levels. Furthermore, there is the preparedness of SPMI documentation, the execution of the quality cycle, and the implementation of Internal Quality Audit by the Audit Team. It is imperative to consistently and sustainably implement SPMI in Indonesian Higher Education Institutions (HEIs). This will lead to an improvement in quality and the ability to satisfy stakeholders through the effective execution of the University's trifocal functions, namely teaching, research, and services.